Justice for animals : our collective responsibility - Nussbaum, Martha C. (Martha Craven), 1947- (Simon & Schuster, 2022)
"A revolutionary new theory and call to action on animal rights, ethics, and law from the renowned philosopher Martha C. Nussbaum"--